2015
DOI: 10.1021/acs.jctc.5b00558
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Fragment Based ab Initio Molecular Dynamics for Proteins

Abstract: Developing ab initio molecular dynamics (AIMD) methods for practical application in protein dynamics is of significant interest. Due to the large size of biomolecules, applying standard quantum chemical methods to compute energies for dynamic simulation is computationally prohibitive. In this work, a fragment based ab initio molecular dynamics approach is presented for practical application in protein dynamics study. In this approach, the energy and forces of the protein are calculated by a recently developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 63 publications
0
64
0
Order By: Relevance
“…144146 Ideas have been proposed for nonempirically incorporating short-range nonbond repulsions by introducing inter-fragment orthogonality restraints into X-Pol 147 but practical applications of those ideas have not yet been explored.…”
Section: Inter-fragment Coupling Schemesmentioning
confidence: 99%
See 2 more Smart Citations
“…144146 Ideas have been proposed for nonempirically incorporating short-range nonbond repulsions by introducing inter-fragment orthogonality restraints into X-Pol 147 but practical applications of those ideas have not yet been explored.…”
Section: Inter-fragment Coupling Schemesmentioning
confidence: 99%
“…Another approach to avoid using Ewald’s method with ab initio Hamiltonians include the Reaction Field method; 186,187 however, the predominant choice continues to be the use of real-space electrostatic truncation. 127,146,188194 …”
Section: Long-ranged Electrostatic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic structures exhibited by transition-metal complexes are so diverse that it is very difficult to represent them in an unbiased benchmark set. If accurate reference data for the chemical system of interest were available, one could not even assume the error of a DFT result to be constant among homologous molecules [23,27]. In a recent study [23], we showed that popular density functionals struggle to reproduce experimental ligand dissociation energies of large organometallic transition-metal complexes in our WCCR10 reference set.…”
Section: Introductionmentioning
confidence: 99%
“…69,70,7276 However, applications of ab initio QM/MM often still forego the use Ewald summations, preferring instead to model the long-range electrostatic with a reaction field method 77,78 or perform real-space electrostatic truncation, shifting, or smoothing. 5254,7984 Recent work has advocated a 22 Å real-space switched electrostatic cutoff method using the minimum image convention. 85 Regrettably we’ve noticed that many authors have failed to report the size of the QM/MM nonbond cutoff that they’ve used, and other details defining how the electrostatics were performed.…”
Section: Introductionmentioning
confidence: 99%